Investigating Indonesian Students Entrepreneurial Intention: The Mediating Role of Entrepreneurial Attitude - Budi Eko Soetjipto; Dwi Hasmidyani; Wahjoedi Wahjoedi; Hari Wahyono (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2022)
This paper investigates the mattering predictor of students’ entrepreneurial attitudes and intentions among Indonesian university students. The research involves some variables, including subjective norms, entrepreneurship education and entrepreneurial environment as a predictor of attitudes and intentions for entrepreneurship. To understand the relationship between variables, this study incorporates explanatory research using structural equation analysis. The data were gathered undergoing online questionnaires, which were provided in Google form and distributed to participants via WhatsApp. The findings indicate that students’ entrepreneurial attitude can be performed by entrepreneurship education, entrepreneurial environment and subjective norms. This finding also points out a significant link between entrepreneurial attitudes and entrepreneurial intentions. Additionally, students’ intention for entrepreneurship can be explained by subjective norms and the entrepreneurial environment. However, this finding confirms that entrepreneurship education failed in determining students’ intention for entrepreneurship. Lastly, this study also confirms the role of entrepreneurial attitudes in mediating entrepreneurship education, subjective norms and intention for entrepreneurship. Keywords: Entrepreneurial Attitudes, Entrepreneurial Intention, Entrepreneurship Education, Entrepreneurial Environment, Subjective Norms